Penggunaan Lagu Liyadani Dalam Bahasa Arab Pada Murid TK Taud Luqmanul Hakim Langsa - Mutia Hanum (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
The aim of this research is to explain the habit of listening to Arabic through liyadani song activities with movements and pointing to body parts, namely the fingers. This research uses qualitative descriptives to present the research results according to the facts at the TAUD Luqmanul Hakim Kindergarten This research uses a qualitative approach. Data collection methods include observation, interviews and documentation. The informants in this research were school principals, teachers and students. Observations were carried out to observe activities inside and outside the classroom regarding understanding the concept of body parts. . From the data obtained, this school already has targeted activities to introduce Arabic to students. One of the efforts to introduce Arabic is through liyadani songs. The teacher has introduced the finger parts to the students but has not yet used Arabic, and by practicing this song the students are able to recognize the finger parts in Arabic.